Architecture and Florogenesis in Female Cannabis sativa Plants - Spitzer-Rimon, Ben; Duchin, Shai; Bernstein, Nirit; Kamenetsky, Rina (Frontiers in Plant Science, 2019)
The inflorescence is the main product of medical cannabis. Hundreds of specialized metabolites with potential bioactivity are produced and accumulated in the glandular trichomes that are highly abundant mainly on female inflorescences. Understanding the morphophysiological and genetic mechanisms governing flower and inflorescence development is therefore of high scientific and practical importance. However, in-depth investigations of cannabis florogenesis are limited. Cannabis producers and researchers consider long photoperiod to be “non-inductive” or “vegetative”, but under these growth conditions, the development of solitary flowers and bracts in shoot internodes clearly indicates that the plant cannot be defined as vegetative or non-inductive in the classical sense. Most probably, induction of solitary flowers is age-dependent and controlled by internal signals, but not by photoperiod. Short photoperiod induces intense branching, which results in the development of a compound raceme. Each inflorescence consists of condensed branchlets with the same phytomer structure as that of the larger phytomers developed under long day. Each phytomer consists of reduced leaves, bracts, one or two solitary flowers, and an axillary shoot (or inflorescence). Therefore, the effect of short photoperiod on cannabis florogenesis is not flower induction, but rather a dramatic change in shoot apex architecture to form a compound racemose inflorescence structure. An understanding of the morphophysiological characteristics of cannabis inflorescence will lay the foundation for biotechnological and physiological applications to modify architecture, and to maximize plant productivity and uniformity in medical Cannabis.